(untitled) (Jurnal Destinasi Pariwisata, 2026)
Abstract Museum Agung Bung Karno is one of the historical and educational tourist attractions in Denpasar City with the potential to increase tourist visits through the implementation of appropriate marketing strategies. However, the number of tourist visits has not yet reached its optimal level, indicating the need for effective marketing strategies to support an increase in visitor arrivals. This study aims to analyze the marketing mix strategy for increasing tourist visits to Museum Agung Bung Karno. This study employed a descriptive approach using qualitative methods supported by quantitative data. Data were collected through observation, interviews, documentation, questionnaires distributed to 79 tourists, and weighting questionnaires completed by three academics specializing in tourism marketing. The data were analyzed using the Internal Factor Analysis Summary (IFAS), External Factor Analysis Summary (EFAS), the Internal–External (IE) Matrix, and the SWOT Matrix. The findings indicate that Museum Agung Bung Karno obtained an IFAS score of 2.91 and an EFAS score of 3.17, placing the museum in Cell II of the IE Matrix, which represents the Grow and Build position. These findings indicate that the museum possesses relatively strong internal conditions supported by favorable external opportunities. Based on the SWOT analysis, the priority strategy is the Strengths–Opportunities (SO) strategy, which includes developing history-based educational tourism programs through collaboration with various stakeholders, utilizing government support to strengthen the museum’s role as a historical and educational tourism destination, and optimizing digital promotion to enhance the museum’s attractiveness and increase tourist visits.